Consumer protection from false advertising - BRAHIMI, Hania (Journal of Human Sciences, 2020)
Economic openness has led to the expansion of the competitive market and as a result of the diversity and multiplicity of goods and services, the imitation of the brand has become easy, which affects the security, health and interest of the consumer. Commercial advertising has become an important pattern in the lives of producers and trade. To promote products as it is a link between the product or service and the consumer provided that it is free from lying and misleading, so it was necessary to lay the foundations and rules for the form and how to commercialize and put them under legal and legitimate controls to protect consumer satisfaction in the stage before contracting and to strengthen the center E in front of the strength and experience of economic aid, which seeks to achieve profit by any means, even at the expense of the consumer.